Caught in a whirlwind : a cultural history of Ottoman Baghdad as reflected in its illustrated manuscripts - Taner, Melis (The Iberian Religious World, 2020)
Caught in a Whirlwind: A Cultural History of Ottoman Baghdad as Reflected in its Illustrated Manuscripts focuses on a period of great artistic vitality in the region of Baghdad, a frontier area that was caught between the rival Ottoman and the Safavid empires. In the period following the peace treaty of 1590, a corpus of more than thirty illustrated manuscripts and several single page paintings were produced. In this book Melis Taner presents a contextual study of the vibrant late sixteenth-century and early seventeenth-century Baghdad art market, opening up further avenues of research on art production in provinces and border regions.